A Person-Centered Perspective on the Role of Peer Support and Extreme Peer Orientation in Youth with Type 1 Diabetes: A Longitudinal Study. Issue 11 (24th April 2020) - Raymaekers, Koen; Prikken, Sofie; Oris, Leen; Vanhalst, Janne; Moons, Philip; Goossens, Eva; Weets, Ilse; Luyckx, Koen
Abstract: Background: Despite clear evidence that peers are crucial for youth development, research on the role of peers for youth with Type 1 diabetes (T1D) is scarce. Purpose: The present study identified trajectory classes of perceived peer functioning in youth with T1D, based on peer support and extreme peer orientation (EPO). Further, classes were compared with respect to their trajectories of depressive symptoms, diabetes-specific distress, treatment adherence, and HbA1c values. Methods: Five hundred and fifty-nine youth (14–25 years) with T1D completed questionnaires at baseline, 1, 2, and 3 years later. Latent class growth analysis identified classes of perceived peer functioning. Multigroup latent growth curve modelling assessed whether these classes were characterized by different trajectories of general and diabetes-specific functioning. Results: A socially normative class (48%) was characterized by trajectories of high support and low EPO over time. A socially reserved class (29%) was characterized by low support and EPO, and a socially oriented class (17%) by high support and EPO. Finally, a socially vulnerable class (6%) was characterized by low support and high EPO. The normative class functioned significantly better over time than the other classes. The vulnerable class functioned significantly worse compared to the reserved class, despite experiencing equally low levels of support. Conclusions: The results underscore the need to take youths' orientation toward the peer context into account alongside support when tapping into the role of peers, because individuals with low levels of support and EPO functioned substantially better than individuals with similar low levels of support but high levels of EPO. Abstract : Some youth with type 1 diabetes struggle to adaptively fit in with their peers. They have much worse mental and physical health than youth with healthy peer relationships.